A cowboy for Christmas - Richardson, Sara (Romance fiction writer); Ryan, R. C., 1937- (Richardson, Sara (Romance fiction writer). Rocky Mountain Riders novel., 2019)
When the beloved Farm Café in Topaz Falls burns to the ground, widow Darla Michaels comes up with the perfect plan to help her friends rebuild -- a Cowboy Christmas Festival complete with a sexy bachelor auction and a benefit rodeo. But to pull it off, she has to pretend to be engaged to Ty Forrester, the irresistible bull rider who keeps testing her keep-things-casual policy. A fake fiancée wasn't on Ty's Christmas list this year, but it's the only way to get his family to visit over the holidays so his NFL-star brother can draw more tourists to the festival. The engagement wouldn't be such a problem if Ty wasn't starting to have real feelings for Darla. Knowing he can't go on pretending, Ty prepares to tell his family the truth-but then he and Darla discover a precious little Christmas surprise that just might help them embrace a whole new life together.